# How do you simplify #sqrt(4a^6)#?

##### 3 Answers

#### Explanation:

The square root of

need to divide the given exponent by the value of the root required:

So:

#### Explanation:

The expression which we have is:-

It can also be written as

The final answer is:

#### Explanation:

Note that:

#(2a^3)^2 = 2^2(a^3)^2 = 4a^6#

So *a* square root of

Note that:

#(-2a^3)^2 = 4a^6#

So

What do we mean when we write

So long as the radicand is non-negative, then these symbols refer to the principal non-negative square root.

For any real value of

Note however that

So in order to cover all real values of

#sqrt(4a^6) = abs(2a^3)#

If, in addition we are told that

#sqrt(4a^6) = 2a^3#